Optimized framework for evaluating F3 transgressive segregants in cayenne pepper - Ifayanti Ridwan; Muh Farid; Feranita Haring; Nuniek Widiayani; Ahmad Yani; Nirwansyah Amier; Muhammad Alfan Ikhlasul Amal; Jekvy Hendra; Nawab Ali; Mekhled Mohamed Alenazi; Mahmoud F. Seleiman; Willy Bayuardi Suwarno; et al. (BMC Plant Biology)
Abstract Developing F3 transgenic segregants has significant potential to improve cayenne pepper varieties. However, current evaluation methods are often inconsistent and inaccurate, hindering the identification of effective traits. Traditional approaches only focus on a few aspects, thus not covering the full potential performance of the genotype. Utilizing morphometric image processing and categorical parameter assessment can fill the gap of traditional approaches to improving accuracy and objectivity in evaluation. In addition, environmental factors affecting the evaluation process are not adequately considered, making the results unreliable. Therefore, a systematic evaluation framework integrating morphometric analysis, categorical assessment, and environmental correction is essential for optimizing F3 cayenne transgressive segregants. The study aims to develop a synchronized assessment and selection approach based on agronomic, fruit morphometric, and categorical traits in evaluating F3 cayenne transgressive segregants. This research was designed with a randomized completed block design with 16 transgressive segregant genotypes and three check varieties. Each genotype was repeated three times, resulting in 57 experimental units. Based on the results of this study, quantitative and categorical indices could be used to selectively and systematically evaluate potential transgressive segregants in F3 cayenne peppers. The quantitative index is formed from outcome selection criteria, number of productive branches, area, and major axes weighted through an unbiased linear estimation approach, heritability, and best path analysis. Seven genotypes demonstrated superior transgressive performance based on quantitative indices, with G10.9.2, G10.7.1, and G6.8.5 excelling in both agronomic traits and categorical evaluations. These lines can be recommended for yield evaluation and hybrid cross-parents.